2013
DOI: 10.1016/j.gene.2012.09.130
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte BMP2 signaling plays an essential role in bone fracture healing

Abstract: The specific role of endogenous Bmp2 gene in chondrocytes and in osteoblasts in fracture healing was investigated by generation and analysis of chondrocyte- and osteoblast-specific Bmp2 conditional knockout (cKO) mice. The unilateral open transverse tibial fractures were created in these Bmp2 cKO mice. Bone fracture callus samples were collected and analyzed by X-ray, micro-CT, histology analyses, biomechanical testing and gene expression assays. The results demonstrated that the lack of Bmp2 expression in cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 49 publications
4
54
0
Order By: Relevance
“…Taking into account the results of our in vivo study 2 weeks postoperatively, this supports the hypothesis that non-union formation is due to a reduced expression of osteogenic growth factors such as e.g. BMP-2/-4/-6/-7 during the early stage of bone healing (Mi et al, 2013;Cheng et al, 2003;Tsuij et al, 2006;Schmidmaier et al, 2002;Garcia et al, 2012;Schwabe et al, 2014). Although we do not have any data on BMP-2 release from MCM in vivo, our study demonstrates for the first time that the release of BMP-2 from MCM generates healing in a challenging non-union model.…”
Section: Orth Et Al Bmp-2-coated MCM and Bone Repairsupporting
confidence: 86%
See 2 more Smart Citations
“…Taking into account the results of our in vivo study 2 weeks postoperatively, this supports the hypothesis that non-union formation is due to a reduced expression of osteogenic growth factors such as e.g. BMP-2/-4/-6/-7 during the early stage of bone healing (Mi et al, 2013;Cheng et al, 2003;Tsuij et al, 2006;Schmidmaier et al, 2002;Garcia et al, 2012;Schwabe et al, 2014). Although we do not have any data on BMP-2 release from MCM in vivo, our study demonstrates for the first time that the release of BMP-2 from MCM generates healing in a challenging non-union model.…”
Section: Orth Et Al Bmp-2-coated MCM and Bone Repairsupporting
confidence: 86%
“…MCM are electrolyte-coated hydroxyapatite particles that are able to bind growth factors, such as Bone Morphogenetic Protein-2 (BMP-2). Bone morphogenetic proteins have been shown to play an important role in fracture healing (Mi et al, 2013). BMP-2 is a member of the transforming growth factor-β superfamily and induces bone formation in vivo (Huang et al, 2008).…”
Section: Orth Et Al Bmp-2-coated MCM and Bone Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process of bone formation, BMP2 plays an important role in inducing transient cartilage that is replaced by bone. This is seen in new bone formation in embryos,10 in tissue engineering11 and during fracture healing 12 13. During osteophyte formation in OA, BMP2 might be involved in a similar process 14…”
Section: Introductionmentioning
confidence: 99%
“…Anadara granosa shells also contain other minerals, such as CaC (98.7%), Mg (0.05%), Na (0.9%), P (0.02%) and other elements (0.2%). 1 Similarly, a research conducted by Hafisko et al 18 showed that Anadara granosa shells contains CaCO3 that can be converted into more biocompatible hydroxyapatite compounds than calcium carbonate alone, so the process is more osteoconductive conditioned by inducing BMP-2. BMP-2 can increase the differentiation of periosteal cells, derivatives of mesenchymal stem cell (MSC) in the formation of chondroblasts and osteoblas.…”
mentioning
confidence: 99%